2015
DOI: 10.3324/haematol.2015.127902
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepcidin in transferrin-treated thalassemic mice correlates with increased liver BMP2 expression and decreased hepatocyte ERK activation

Abstract: Iron overload results in significant morbidity and mortality in β-thalassemic patients. Insufficient hepcidin is implicated in parenchymal iron overload in β-thalassemia and approaches to increase hepcidin have therapeutic potential. We have previously shown that exogenous apo-transferrin markedly ameliorates ineffective erythropoiesis and increases hepcidin expression in Hbb th1/th1 (thalassemic) mice. We utilize in vivo and in vitro systems to investigate effects of exogenous apo-transferrin on Smad and ERK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…Although chronic dietary iron loading and deficiency modulated BMP2 expression, BMP2 levels were not changed by an isolated increase in serum iron and transferrin saturation in response to oral iron gavage. Although a prior report suggested that liver BMP2 may be modulated by apo‐transferrin administration, we were not able to validate the specificity of BMP2 antibody used in that study using our Bmp2 fl/fl ;Tek‐Cre + mice (data not shown) . A similar lack of modulation by serum iron was also seen for BMP6, at least at the mRNA level, as previously reported .…”
Section: Discussionsupporting
confidence: 47%
“…Although chronic dietary iron loading and deficiency modulated BMP2 expression, BMP2 levels were not changed by an isolated increase in serum iron and transferrin saturation in response to oral iron gavage. Although a prior report suggested that liver BMP2 may be modulated by apo‐transferrin administration, we were not able to validate the specificity of BMP2 antibody used in that study using our Bmp2 fl/fl ;Tek‐Cre + mice (data not shown) . A similar lack of modulation by serum iron was also seen for BMP6, at least at the mRNA level, as previously reported .…”
Section: Discussionsupporting
confidence: 47%
“…We hypothesized that SMURF1‐mediated HAMP suppression was dependent on ERK1/2 signalling. ERK1/2 signalling results in the phosphorylation of the SMAD linker domain for polyubiquitination by SMURF1, and degradation (Sapkota et al , ), and we have previously demonstrated activation of ERK1/2 signalling in hepatocytes from β‐thalassaemic mice, a mouse model in which HAMP regulation is dominated by erythropoiesis (Chen et al , ). Thus, the evaluation of ERK1/2 signalling demonstrated that ERK1/2 phosphorylation is increased by GDF11 in a dose‐dependent manner (Fig A), but not affected by SMURF1 overexpression (Figure S6C).To further explore whether ERK signalling is required for GDF11‐triggered BMP‐suppression of SMAD signalling, we treated Huh7 cells with GDF11 with or without U0126, a MEK/ERK1/2 inhibitor (Fig B, ).…”
Section: Resultsmentioning
confidence: 90%
“…Mouse primary hepatocytes were obtained from C57BL/6 (wild‐type; WT) mice by two‐step liver perfusion. In brief, the mouse livers were perfused by collagenase IV (Sigma, St. Louis, MO, USA) and 250 000 cells/well were plated on collagen‐coated 6‐well plates in DMEM supplemented with 5% FBS, and cultured as previously described (Chen et al , ). For experiments using rGDF11, Peprotech [Rocky Hill, NJ, USA] or R&D Systems [Minneapolis, MN, USA]), hepatocytes were incubated with 5% FBS and increasing doses of rGDF11 for 24 h. The specific MEK/ERK1/2 inhibitor, U0126 (Promega, Madison, WI, USA), was applied 2–2·5 h prior to cell harvest, and the proteasome inhibitor MG132 (Sigma) was added 4–6 h before cell harvest.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, in a mouse model of β thalassemia, transferrin treatment normalized labile plasma iron levels and RBC survival, and increased hepcidin expression[62]. In addition, increased hepcidin levels were accompanied by increased BMP2 expression in the liver and concomitant decrease in extracellular-signal related kinase (ERK) activation[63]. …”
Section: Hematological Disorders and Phmentioning
confidence: 99%